Best Practices for Automated Traceability. - Cleland-Huang, Jane; Settimi, Raffaella; Romanova, Eli; Berenbach, Brian; Clark, Stephen (Computer (00189162), 2007)
The article discusses automated traceability, a method for software engineers to design and maintain software systems. Automated traceability utilizes information-retrieval methods to reduce manual efforts in creating a requirements trace matrix. Manual traces are often inconsistent or incomplete and often cannot be applied to supplemental documents. Probabilistic network-based algorithms increase accuracy in the assessment of candidate links. The authors suggest traceability frameworks function better if designed for a specific purpose and with an appropriate level of granularity. Creating a project glossary and an informational hierarchy can aid in the creation of traceable artifacts.